An overview of the use of food-based Newcastle disease vaccine in Malaysia. - Ibrahim, Abdul Latiff; Ideris, Aini; Babjee, Ahmad Mustafa (1991)
Since 1985, Universiti Pertanian Malaysia (UPM) has been involved in two research projects funded by AClAR. The main objective of these projects was to develop a new. simple and effective Newcastle disease (NO) vaccine for village poUltry. Many trials or experiments were conducted and these included: • selecting and cloning a heat tolerant variant of the V 4-ND virus (NDV) which was used as vaccine; • preparation and testing of food-based ND vaccine using various food grains as carriers of the vaccine; • determining the efficacy of the food-based vaccine under laboratory. simulated village and field conditions; • transfer of technology; • a large scale control program incorporating epidemiological study and analysis of economic benefits; and • application of vaccine for commercial broilers and layers. It has now been established that village chickens vaccinated with the vaccine are protected against challenge with virulent NDV. The benefits to the rural farmers resulting from the vaccine include increased survival of chickens and increased income.